Maatalouden ympäristöohjelma 1995-1999:n vaikutus keinolannoitteiden käyttöön - ekonometrinen analyysi - Peltola, Jukka (Maatalouden taloudellinen tutkimuslaitos, 1999)
In this study, effects of Finnish Agri-Environmental Programme (FAEP) on input demand are reviewed. More specifically, changes in demand of main nutrients, nitrogen (N), phosphorous (P) and potassium (K) are studied. Measuring and valuing non-point source pollution itself is a very difficult task, therefore, it was seen to be more fruitful to determine changes in the demand of polluting inputs. It is clear that changes in amounts of inputs demanded do not guarantee similar changes in leaching, as farming practices, weather, attitudes, as well as many other things affect the leaching. Generally speaking it can be assumed, however, that decreased use of fertilizers also shows in decreased leaching. The main features of the FAEP and main components in farmer s decision making are reviewed first. Next, a history of artificial fertilizer use in recent decades is presented. After that, demand of nitrogen, phosphorous and potassium is analyzed. As a method in the analysis a normal linear regression is used. The demand is evaluated per-hectare basis, first, using an aggregated nation level data, and secondly, for nitrogen and phosphorous, using data divided by agricultural centers. As a main observation, it can be said, that per-hectare-demand of nitrogen and phosphorous started to decline in the end of the eighties. At the time of joining into the EU in the 1995, the demand of these nutrients actually peaked again. However, the year 1996 FAEP started to take an effect, and nutrient demands started decrease, nitrogen already during the crop year 1995-1996 and phosphorous 1996-1997. The demand of potassium is not visibly affected. This is logical as the use of potassium is not directly regulated in the FAEP. In the regional analysis, the main observation is that the demand of nitrogen and phosphorus have been mostly affected in the Central and Northern Finland, except in Lapland. In the Southern Finland, the demand of nitrogen decreased more than forecasted in some regions, but the demand of phosphorus was not affected.
Effects of Finnish agri-environmental programme on demand for main nutrients
Keywords: Ma; maatalouden ympäristöohjelma; keinolannoitteet; ekonometrinen analyysi; demand for nutrients; fertilizer demand; Finnish agri-environmental programme